The Transcriptomic Signature of RacA Activation and Inactivation Provides New Insights into the Morphogenetic Network of Aspergillus niger - Kwon, Min Jin (Public Library of Science, 2013)

(untitled)
RacA is the main Rho GTPase in Aspergillus niger regulating polarity maintenance via controlling actin dynamics. Both deletion and dominant activation of RacA (Rac(G18V)) provoke an actin localization defect and thereby loss of polarized tip extension, resulting in frequent dichotomous branching in the ΔracA strain and an apolar growing phenotype for Rac(G18V). In the current study the transcriptomics and physiological consequences of these morphological changes were investigated and compared with the data of the morphogenetic network model for the dichotomous branching mutant ramosa-1. This integrated approach revealed that polar tip growth is most likely orchestrated by the concerted activities of phospholipid signaling, sphingolipid signaling, TORC2 signaling, calcium signaling and CWI signaling pathways. The transcriptomic signatures and the reconstructed network model for all three morphology mutants (ΔracA, Rac(G18V), ramosa-1) imply that these pathways become integrated to bring about different physiological adaptations including changes in sterol, zinc and amino acid metabolism and changes in ion transport and protein trafficking. Finally, the fate of exocytotic (SncA) and endocytotic (AbpA, SlaB) markers in the dichotomous branching mutant ΔracA was followed, demonstrating that hyperbranching does not per se result in increased protein secretion.